Age Related Changes in Body Weight and Gonadal Size in Jersey x Kankrej Crossbreds From Birth to Puberty - SINGH, S K; LAISHRAM; PATEL, J M (The Indian Journal of Animal Reproduction, 2023)
Gonadal growth relative to age and body weight changes was studied in 40 Jersey X Kankrej crossbred male calves by collecting testes at different ages starting from birth to 16 months of age. Paired testicular weight (PTW) at birth was 4.52±0.92 gm which increase to 16.77±2.19 to 38.43±9.55 gm at 5 and 8 month of age. Thereafter it grew rapidly and attained 107.67 ±23.90 and 442.80±41.46 gm at 12 and 16 month of age respectively. The length, width, thickness and circumference of testes showed steady growth indicating constant shape. Highly significant (P < 0.01) and positive correlation of age and body weight with PTW and other testicular biometrics were recorded. Equation for predicting PTW and testicular circumference from age and body weight have been developed.